A fatal winter a Max Tudor novel - Malliet, G. M., 1951- (Malliet, G. M., 1951- Max Tudor novel., 2012)
Max--Anglican priest, former MI5 agent, and village heartthrob--investigates two deaths at Chedrow Castle. But his growing attraction to Awena Owen complicates his case, as does the recent arrival at Chedrow Castle of a raucous group of long-lost, greedy relatives, any one of whom has a motive for murder.